Considerations for the design and conduct of externally controlled trials for drug and biological products - A. S. Motrinchuk; D. Yu. Belousov (Реальная клиническая практика: данные и доказательства, 2023)
This guidance provides recommendations to sponsors and investigators considering the use of externally controlled clinical trials to provide evidence of the safety and effectiveness of a drug product. In an externally controlled trial, outcomes in participants receiving the test treatment according to a protocol are compared with outcomes in a group of people external to the trial who had not received the same treatment. The external control arm can be a group of people, treated or untreated, from an earlier time (historical control), or it can be a group of people, treated or untreated, during the same period (concurrent control) but in another setting. The guidance addresses considerations for the design and analysis of externally controlled trials to study the effectiveness and safety of drugs, including discussion of threats to the validity of trial results from potential bias. Although various sources of data can serve as the control arm in an externally controlled trial, this guidance focuses on the use of patient-level data from other clinical trials or from real-world data (RWD) sources, such as registries, electronic health records, and medical claims. The guidance also describes considerations related to communicating with the FDA and ensuring access by the FDA to data from an externally controlled trial. This guidance does not address other types of external controls, such as using summary-level estimates instead of patient-level data. This guidance does not discuss details of the design and analysis of a natural history study nor the reliability and relevance of various sources of RWD that could be used in an externally controlled trial. Finally, this guidance also does not discuss considerations for using external control data to supplement a control arm in a traditional randomized controlled clinical trial. In general, FDA guidance documents do not establish legally enforceable responsibilities. Instead, guidance describes the Agency’s current thinking on a topic and should be viewed only as recommendations, unless specific regulatory or statutory requirements are cited. The use of the word should in Agency guidance means that something is suggested or recommended, but not required.